IMPROVING THE QUALITY OF COMMUNITY SERVICES ESPECIALLY PASSPORT ISSUANCE THROUGH EAZY PASSPORT ACTIVITIES IN THE AREA IMMIGRATION OFFICE CLASS I BORDER CONTROLI BALIKPAPAN - Lidya Marsaulina Siregar; Vita Nurul Fathya (Jurnal Abdimas Imigrasi, 2021)
Improving the quality of public services, especially in the process of issuing passports, requires innovation and policies that support easy access by every community. One of the policies that have been implemented nationally is the collective passport issuance pick-up service known as the Eazy Passport. This service is an innovation that expects the willingness of people who want to have a passport but do not want to come to the Immigration Office alone. The Eazy Passport service can be submitted by agencies, government offices, or communities who wish to submit a collective passport application. Data collection and other necessary things that are usually done at the Immigration Office can be done easily at a mutually agreed location. Eazy Passport activities that have been submitted to the Immigration Office will be carried out on the specified date by bringing the necessary equipment and supplies. This activity was carried out at the Regional Office of the Directorate General of Taxes in East Kalimantan, Ministry of Finance. This activity was welcomed by employees and their families and relatives who registered with the Immigration Office regarding the issuance of their passports. These passport applicants no longer need to carry the necessary files and equipment when carrying out biometric data collection activities so that the implementation runs effectively and efficiently and speeds up the passport issuance process